Tratamiento de recesiones gingivales con injerto de tejido conectivo subepitelial y técnica del sobre: reporte de caso - Cruz Morales, Rosario (2020)
The objective of this case presentation is to describe the use of the envelope technique with subepithelial connective tissue graft in the treatment of two Miller gingival recessions (class I and II) located at 44 and 45. This case is a 50-year-old male patient, who went to the Periodontics service of the "III Congress of the PCC" Stomatology Clinic, Matanzas, Cuba, for "a change of the position of the gum in some teeth". Clinically, there was root exposure in 44 and 45, without the presence of periodontal pockets or radiographic changes. Localized Miller class I gingival recession was diagnosed in 44 and Miller class II in 45. A subepithelial connective tissue graft and a coronal displaced envelope flap were performed. At fifteen days, in the receiving area, there was edema, complete root coverage of 45 and 2 mm of exposed root in 44. At six months, periodontal condition of 44 has been improved. After two years, the exposed roots were completely covered, with positioned gingival tissue, inserted gingiva gain and color mimicry between grafted site and adjacent area. It is concluded that this technique achieved satisfactory results in the treatment of gingival recessions of 44 and 45.